Cult of Two - Faudet, Michael (Andrews McMeel Publishing, 2019)
Cult of Two is the fifth book of internationally bestselling poet Michael Faudet, author of Winter of Summers, Smoke & Mirrors, Bitter Sweet Love, and Dirty Pretty Things--a finalist in the Goodreads Readers Choice awards. His intimate writing style and exquisite ability to paint pictures with words has captured the imagination and hearts of thousands of people from around the world.